Use of Children's Literature in the Process of the classroom - Shokirova Maftuna Botirjon Qizi (Peerian Journals Publishing, 2022)
In the article, opinions were expressed about the use of children's literature in the process of extracurricular reading in elementary school reading classes.
Keywords: aesthetics; education; folklore; instruction